2013
DOI: 10.4067/s0034-98872013000500007
|View full text |Cite
|
Sign up to set email alerts
|

Estudio temporal de diabetes mellitus tipo 1 en Chile: asociación con factores ambientales durante el período 2000-2007

Abstract: (Rev Med Chile 2013; 141: 595-601).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Epidemiologic studies strongly suggest that exposure to air pollution can increase both the incidence and severity of autoimmune disease (Farhat et al, 2011; Gawda et al, 2017). Specifically, exposure to PM 1 in the atmosphere aggravates type 1 diabetes, rheumatoid arthritis, and multiple sclerosis, among others (Angelici et al, 2016; Beyerlein et al, 2015; Brook et al, 2013; Chang et al, 2016; Di Ciaula, 2016; Gonzalez et al, 2013; Gregory et al, 2008; Hathout et al, 2002; Malmqvist et al, 2015; Oikonen et al, 2003; Roux et al, 2017; Vojinovic et al, 2015). Although strong correlations exist connecting PM exposure to autoimmune disease, identifying mechanisms leading to this disease process has proven particularly difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic studies strongly suggest that exposure to air pollution can increase both the incidence and severity of autoimmune disease (Farhat et al, 2011; Gawda et al, 2017). Specifically, exposure to PM 1 in the atmosphere aggravates type 1 diabetes, rheumatoid arthritis, and multiple sclerosis, among others (Angelici et al, 2016; Beyerlein et al, 2015; Brook et al, 2013; Chang et al, 2016; Di Ciaula, 2016; Gonzalez et al, 2013; Gregory et al, 2008; Hathout et al, 2002; Malmqvist et al, 2015; Oikonen et al, 2003; Roux et al, 2017; Vojinovic et al, 2015). Although strong correlations exist connecting PM exposure to autoimmune disease, identifying mechanisms leading to this disease process has proven particularly difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Hathout et al (20) found pre-diagnosis PM 10 exposure was significantly higher in children diagnosed before 5 years of age compared to healthy controls. Likewise, a study from Chile found that PM 2.5 levels were associated with the onset of T1D in children (19). Beyerlein et al (16) analyzed data from a population-based register monitoring incidence of diabetes in children and youths in Germany since 2009 and found that high exposure to the traffic-related air pollutants PM 10 , NO 2 , and possibly PM 2.5 accelerated the manifestation of T1D, but only in very young children.…”
Section: Particulate Mattermentioning
confidence: 94%
“…To evaluate the impact of PM2.5 on the occurrence of T1D Gonzáles et al [96] reviewed data of children and adolescents with T1D at onset who received their first insulin injection between 2000 and 2007. Comparing these data with the PM rates obtained from Environmental Services they demonstrated a significant increase of relative risk related to PM2.5 showing that air pollution factors could be related to peaks of T1D incidence.…”
Section: Human Studiesmentioning
confidence: 99%